Space Physics Career in a Developing Country: Opportunities and Challenges - González-Esparza, J. Américo (Frontiers in Astronomy and Space Sciences, 2022)
The development of an infrastructure of observational instruments is a great challenge for any young scientist especially working in a country where this is a new field of scientific knowledge and the funds are limited. However, I argue that although it can be questionable in terms of all the difficulties that you might face, the observational infrastructure is a crucial aspect of building a local scientific community. Therefore, it should be pursued as a national priority.